A Study of Socio-Demographic Profile, Health Profile and Awareness on Non Communicable Diseases among Urban Population of Ahmedabad, Gujarat - Kapil J Govani; Amul B Patel (Medsci Publications, 2017)
Introduction: The current epidemic of non-communicable diseases in India is attributed to increased longevity and lifestyle changes resulting from urbanization. Objectives: (1) To assess the socio-demographic & health profile of urban population. (2) To evaluate awareness on risk factors of non communicable diseases (NCD). Methodology: A cross sectional study was conducted among urban population of central and south zone of Ahmedabad municipal Corporation (AMC) area during February to May 2015. Pretested performa was used for study. Among 200 houses, total 517 people were selected for study after their informed consent. Results: Out of 517 people, males were 54.9% & females were 45.1%. Majority of people were belongs to 35 to 45 yr. age group (22.1%). Majority (51.3%) of people had habit of khaini (mixture of tobacco & lime). Majority (45.6%) of them were found sedentary workers. According to study group, ageing was commonest risk factor for NCD. Conclusions: Mean age was 47.3 ± 2.1. Among different NCDs, majority of people were found on medication for Hypertension. Gender wise comparison of body mass index (BMI) shows significant statistical difference.